PENGGUNAAN MEDIA PAPAN SELIP (SLOT BOARD) DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA PERANCIS TINGKAT A1 CECRL DI SMA TELKOM BANDUNG - Juliarti, Annisa Trian; Hardini, Tri Indri; Racmadhany, Ariessa (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
In several learning methods, the Slot Board is believed to be able to solve the difficulties in learning. So in this study the researcher will use Slot Board learning media to determine students' abilities in French speaking skills at A1 CECRL level after using Slot Board media as well as students' opinions regarding learning using Slot Board media in CECRL Level A1 French speaking skills. This research uses a quantitative approach method with a one-shot case study design with datacollection techniques through post-tests and questionnaires distributed to 36 grade 10 students in the 2023/2024 academic year. The results of the research show that the overall point for speaking ability after using this media is 3252/3600, namely getting an average class score of 90.22. With the scores obtained, it can be seen that the class average assessment predicate is very good. The results of the research questionnaire show that the majority of students feel that learning using a slot board really helps the teaching and learning process because the material explained attracts students' attention to be more motivated to learn than usual because it is more fun and easy to pay attention to. Keywords: French speaking skills, slip board, Learning Media.